Enterically delivered insulin tregopil exhibits rapid absorption characteristics and a pharmacodynamic effect similar to human insulin in conscious dogs. Issue 1 (16th September 2018) - Gregory, Justin M.; Lautz, Margaret; Moore, Lindsey M.; Williams, Phillip E.; Reddy, Praveen; Cherrington, Alan D.
Abstract : Aims: Current therapy fails to emulate rapid (first‐phase) insulin release in relation to a meal, a key defect in types 1 and 2 diabetes. We aimed to quantify the pharmacokinetic (PK) and pharmacodynamic (PD) profile of insulin tregopil, an enterically‐absorbed insulin analog that restores the normal distribution of insulin between the hepatic portal and peripheral circulations. Materials and methods: The PK and PD profiles of insulin tregopil were studied in overnight‐fasted, catheterized, conscious canines using four approaches: (1) equimolar intraportal infusions of tregopil vs human insulin; (2) escalating doses of oral tregopil; (3) identical, consecutive enteric doses of tregopil; and (4) comparison of oral tregopil to inhaled and subcutaneous human insulin administration. Results: Equimolar intraportal infusions of tregopil and human insulin resulted in very similar PK profiles and PD profiles were nearly identical. Enteric delivery of tregopil brought about rapid absorption with tmax = 20 minutes in most cases. Median tmax was 20 minutes for oral tregopil and inhaled insulin and 88 minutes for subcutaneous human insulin. The time required for arterial plasma insulin levels to return to baseline was approximately 90, 210 and 360 minutes for oral tregopil, inhaled insulin and subcutaneous insulin, respectively. Conclusions: Enterically delivered tregopil is rapidly absorbed and restores a portal‐to‐peripheral vascular distribution. These characteristics should improve postprandial hyperglycaemia in types 1 and 2 diabetes.